Mandibular Intraosseous Lipoma – Rare and Confusing Lesion - Shareef Araidy; Michael V. Joachim; Ibrahim Shajrawi; Imad Abu El-Naaj (New Advances in Medicine and Medical Science Vol. 2, 2023)
Background: Lipomas can occur anywhere on the body and can be clinically mistaken for other soft tissue lumps. The head and neck are uncommon places for them to occur. Lipomas may undergo varying degrees of involution, with areas of fat necrosis, cyst formation and dystrophic calcification . The most common form of treatment for lipomas is surgical removal, while other options for the condition include liposuction and steroid injections. This chapter aims to present our experience in intraosseous lipoma and review the literature related to it. Case Report: A 38-year-old woman who was initially referred by her dentist because of myofascial pain is detailed in the current study. A mass that was discovered by chance (8*5mm) was successfully removed and identified as an intraosseous lipoma. Excellent painless outcomes and no functional or neurological impairment were caused by the procedure. Both clinically and radiographically, the tumor showed involvement of the inferior alveolar canal. Such unusual tumor traits have never before been documented, disproving earlier hypotheses on the causes of this uncommon malignancy. Conclusion: According to the current case description, this tumor is a real primary benign neoplasm with a definite origin.